In Vitro Evaluation of Oxidative Stress Biomarkers in the Muscle Tissue of Rainbow Trout (Oncorhynchus mykiss Walbaum) Exposed To Leaf Extract of Ficus benjamina L. and ITS Cultivars - Maryniuk, Myroslava; Tkachenko, Halyna; Buyun, Lyudmyla; Kharchenko, Igor; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The goal of this study was to assess in vitro the effect of buffer extract obtained from leaves of Sansevieria caulescens N.E.Br. on the 2-thiobarbituric acid reactive substances (TBARS) as lipid peroxidation biomarker, aldehydic and ketonic derivatives of oxidatively modified proteins, and total antioxidant capacity (TAC) in the muscle tissue of the rainbow trout. Our study suggests that the leaf S. caulescens extract have shown good antioxidant potential in vitro study after incubation with muscle tissue homogenate of rainbow trout. There were no significant changes for TBARS level as biomarker of lipid peroxidation, aldehydic and ketonic derivatives of oxidatively modified proteins between values in control group and in the muscle tissue of rainbow trout after incubation with extracts from leaves of S. caulescens. Our results showed that extract of S. caulescens efficiently increased the total antioxidant capacity in muscle tissue by 46.6 % (p<0.05) due to inhibited the Fe2+/ascorbate-induced oxidation of Tween 80, resulting in a decrease in the TBARS level. Taking into account existing experimental evidence, it is reasonable to assume that secondary plant metabolites, i.e. polyphenolic compounds in the extract of S. caulescens may contribute to the antioxidant activity. Further studies including both the use of other medicinal plants as food additives in aquaculture and the assessment of its antioxidant effects on various tissues are in progress.